Investigation of meteorological conditions and BrO during ozone depletion events in Ny-Ålesund between 2010 and 2021 - B. Zilker; A. Richter; A.-M. Blechschmidt; P. von der Gathen; I. Bougoudis; S. Seo; T. Bösch; J. P. Burrows (Atmospheric Chemistry and Physics, 2023)
During polar spring, ozone depletion events (ODEs) are often observed in combination with bromine explosion events (BEEs) in Ny-Ålesund. In this study, two long-term ozone data sets (2010–2021) from ozonesonde launches and in situ ozone measurements have been evaluated between March and May of each year to study ODEs in Ny-Ålesund. Ozone concentrations below 15 ppb were marked as ODEs. We applied a composite analysis to evaluate tropospheric BrO retrieved from satellite data and the prevailing meteorological conditions during these events. During ODEs, both data sets show a blocking situation with a low-pressure anomaly over the Barents Sea and anomalously high pressure in the Icelandic Low area, leading to transport of cold polar air from the north to Ny-Ålesund with negative temperature and positive BrO anomalies found around Svalbard. In addition, a higher wind speed and a higher, less stable boundary layer are noticed, supporting the assumption that ODEs often occur in combination with polar cyclones. Applying a 20 ppb ozone threshold value to tag ODEs resulted in only a slight attenuation of the BrO and meteorological anomalies compared to the 15 ppb threshold. Monthly analysis showed that BrO and meteorological anomalies are weakening from March to May. Therefore, ODEs associated with low-pressure systems, high wind speeds, and blowing snow more likely occur in early spring, while ODEs associated with low wind speed and stable boundary layer meteorological conditions seem to occur more often in late spring. Annual evaluations showed similar weather patterns for several years, matching the overall result of the composite analysis. However, some years show different meteorological patterns deviating from the results of the mean analysis. Finally, an ODE case study from the beginning of April 2020 in Ny-Ålesund is presented, where ozone was depleted for 2 consecutive days in combination with increased BrO values. The meteorological conditions are representative of the results of the composite analysis. A ...